Differential regulation of long noncoding RNAs by endogenous and exogenous reactive oxygen species-generating prooxidants in NIH3T3 cells - Yoichi Kurokawa; Takashi Honda; Shingo Fujii; Yugo Narisawa; Hirotaka Ogawa; Hiroki Kawashima; Hidenori Tani (PLoS ONE, 2025)
Long noncoding RNAs (lncRNAs) play crucial roles in various cellular processes, including the response to oxidative stress. However, the relationship between oxidants and lncRNA expression remains poorly understood. This study investigated the effects of endogenous and exogenous prooxidants with reactive oxygen species (ROS)-generating activity on lncRNA expression in NIH3T3 cells. We treated cells with various compounds, including food-derived polyphenols and environmental pollutants, for 24 hours and analyzed lncRNA expression. Treatment with 1 μM exogenous prooxidants (1,2,4-benzenetriol or 1,4-naphthoquinone) resulted in a significant increase (>50-fold) in the expression of several lncRNAs, including Snhg4, Kcnq1ot1, Rmst, Neat1, Gt(ROSA)26Sor, and Peg13. Conversely, exposure to endogenous prooxidants (dopamine and adrenaline), certain food-derived polyphenols (chrysin and 3-O-methylquercetin), or 1,2-naphthoquinone led to a significant decrease (<0.5-fold) in Rmst expression. Similarly, Neat1 expression was significantly reduced in the presence of food-derived polyphenols (luteolin, quercetin, and piceatannol). These findings suggest that prooxidants with distinct redox properties differentially regulate lncRNAs and potentially influence oxidative stress responses. Our results provide new insights into the complex interplay between oxidants and lncRNA regulation. This may have implications for understanding oxidative stress-related pathologies and developing novel therapeutic strategies.